Export Marketing of Tea via the Internet - Ramanujam, P. G.; Naidu, B. V. R. (Indian Journal of Marketing, 2011)
The world tea trade has been undergoing several changes during the last few years. Export prices have decreased over the last decade, in part owing to oversupply, while production has increased faster than demand and tea has continued to face competition from other beverages. There is a growing gap between the prices paid to tea growers and those paid by consumers in importing countries. The internet provides a window of opportunity for improving the marketing of agricultural exports in developing countries, as exemplified by the experience in India. Such use can generate significant benefits for producers in terms of reduced transaction costs and expanded market reach. In all aspects of tea production, consumption and export, India has emerged to be the world leader, and is perhaps the only industry where India has retained its leadership over the last 150 years. Internet use by producers in India to market tea is still in its infancy, although some plantations have established websites linked to search engines and other commercial sites. Industry observers in India consider that more plantations might make use of the internet for direct marketing if they were aware of the potential benefits. India's tea industry is optimistic that internet auctions will become well established, especially after the current glut in tea markets comes to an end. In the light of these developments, the present study has been taken up to examine how the internet can facilitate more direct marketing and bypass some intermediaries, thereby allowing producers to retain a larger share of the export price.